Chemical extraction and modification of chitin and chitosan from shrimp shells - Pakizeh, Majid; Moradi, Ali; Ghassemi, Toktam (European polymer journal, 2021)
[Display omitted] Chitin-based materials are one of the most promising abundant polysaccharide biopolymers for developing constructs with advanced functions due to their unique properties; especially in biomedical science and technology. They have versatile applications in pharmaceuticals and biomedicine. Seafood industries produce a large volume of crustacean shells that contains chitin up to about 30% of its volume; a huge waste source with high costs of pollution. These worthy wastes can be converted into additional high grade, low-volume by-products. On commercial scale, chitin/chitosan is mostly extracted chemically from shrimp shells. The present review summarizes the current chemical methods for chitin recovery and production of its most common derivative, the deacetylated form named chitosan, from shrimp shell wastes. The main extraction steps are discussed individually and “should or must to do points” are highlighted. A brief perspective for future researches in this topic are presented at the end.